Environment friendly products: Factors that influence the green purchase intentions among youth in Malaysia / Nazirah Hamim - Hamim, Nazirah (2018)
The study aims to determine the factors that influence green purchase intention towards environment friendly product among youth in Malaysia. Recently, the environmental problem has become one of the most important issues in. Businesses have started to discover that in the future customers' purchase decision will be based on the environmental considerations. A research frame work was proposed by following the study from Afzaal Ali et al (2012). The independent variables in this study consist of organization's green image, environmental knowledge and environment concern while dependent variable is green purchase intention. Furthermore, are survey using the questionnaire of 100 respondents was conducted among youth in Malaysia that age between 15 and 30. The researcher chooses youth for this study is because youth is the young generation of the country and their purchase decision will affect the future of the country. From the findings, the researcher concluded that there is significant relationship between environmental knowledge and environmental concern with green purchase intention. However, organization's green image has no significant relationship with green purchase intention. Due to time constraint and limitation of respondents, there researcher also recommend the future researcher to make a deep study and wider scope of study with a long period of time to have better understanding.